Fish mass immunization against virus with recombinant "spiny" bacterins. Issue 67 (August 2017) - Coll, Julio
Abstract: Bacterins obtained from recombinant bacteria displaying heterologous antigens in its surface coded by prokaryotic rather than eukaryotic expression plasmids (here called "spiny" bacterins or spinycterins), have been used to increase fish immunogenicity of recombinant viral protein fragments. To explore their immunogenicity, five bacterial-specific membrane anchor-motifs characterized in the literature (Nmistic, Mistic, NTD, YAIN and YBEL) were genetically fused to the immunorelevant cystein-free 117 amino acid fragment II from the ORF149 of cyprinid herpes virus 3 (frgIICyHV3 ). The fusion of anchor-motifs to the N-terminus of frgIICyHV3 enriched expression in E.coli outer membranes as demonstrated by ELISA, immunofluorescence and flow cytometry of formaldehyde-fixed recombinant bacteria (spinycterins). Unconventional low-intensity ultrasound inducing mucosal micropores in a reversible non-harmful manner was used before carp or zebrafish immersion on spinycterin suspensions as a practical delivery alternative to fish-to-fish injection. After ELISA screening for anti-frgIICyHV3 -specific antibodies of spinycterin-immunized fish plasma, the YBEL constructs were identified as the most immunogenic in both carp and zebrafish, correlating with one of the best expressed recombinant proteins as demonstrated by Western blot and surface enriched as demonstrated by ELISA and flow cytometry. The use of prokaryotic expression plasmids to express viral immunorelevant protein fragments in traditionally used fish vaccination bacterins should reduce the environmental concerns raised by DNA vaccination based on eukaryotic expression plasmids. Therefore, spinycterins may be a useful alternative to develop safer fish viral vaccines and mass vaccination methods. Graphical abstract: Highlights: Recombinant bacterins displaying surface viral proteins increase their fish immunogenicity. Prokariotically-made cystein-free recombinant viral small proteins increase safety. Low-intensity ultrasound pulses before small fish immersion in spinycterins favours delivery.